AMPK-induced novel phosphorylation of RUNX1 inhibits STAT3 activation and overcome imatinib resistance in chronic myelogenous leukemia (CML) subjects - Meher Bolisetti Gayatri; Rama Krishna Kancha; Abhayananda Behera; Dorababu Patchva; Nagaraj Velugonda; Sadasivudu Gundeti; Aramati Bindu Madhava Reddy (Cell Death Discovery, 2023)
Abstract Imatinib resistance remains an unresolved problem in CML disease. Activation of JAK2/STAT3 pathway and increased expression of RUNX1 have become one reason for development of imatinib resistance in CML subjects. Metformin has gained attention as an antileukemic drug in recent times. However, the molecular mechanism remains elusive. The present study shows that RUNX1 is a novel substrate of AMP-activated kinase (AMPK), where AMPK phosphorylates RUNX1 at Ser 94 position. Activation of AMPK by metformin could lead to increased cytoplasmic retention of RUNX1 due to Ser 94 phosphorylation. RUNX1 Ser 94 phosphorylation resulted in increased interaction with STAT3, which was reflected in reduced transcriptional activity of both RUNX1 and STAT3 due to their cytoplasmic retention. The reduced transcriptional activity of STAT3 and RUNX1 resulted in the down-regulation of their signaling targets involved in proliferation and anti-apoptosis. Our cell proliferation assays using in vitro resistant cell line models and PBMCs isolated from CML clinical patients and normal subjects demonstrate that metformin treatment resulted in reduced growth and improved imatinib sensitivity of resistant subjects.